2016
DOI: 10.1186/s40478-016-0277-8
|View full text |Cite
|
Sign up to set email alerts
|

CSF complement 3 and factor H are staging biomarkers in Alzheimer’s disease

Abstract: IntroductionCSF levels of established Alzheimer’s disease (AD) biomarkers remain stable despite disease progression, and non-amyloid non-tau biomarkers have the potential of informing disease stage and progression. We previously identified complement 3 (C3) to be decreased in AD dementia, but this change was not found by others in earlier AD stages. We hypothesized that levels of C3 and associated factor H (FH) can potentially distinguish between mild cognitive impairment (MCI) and dementia stages of AD, but w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 41 publications
0
33
0
Order By: Relevance
“…Its release and effects are thus complex, and IL-10 does not exist or act in isolation. Lower IL-10 levels in NC + may be interpreted as a failure in anti-inflammatory processes associated with onset of pathologic AD, or alternatively balanced anti- and proinflammatory responses in asymptomatic AD (e.g., we previously showed complement activation to accompany the MCI + to AD transition [ 18 ]). Similarly, higher IL-10 levels in AD than NC + and MCI + may represent exaggerated anti-inflammatory responses or appropriate IL-10 response to AD-related neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Its release and effects are thus complex, and IL-10 does not exist or act in isolation. Lower IL-10 levels in NC + may be interpreted as a failure in anti-inflammatory processes associated with onset of pathologic AD, or alternatively balanced anti- and proinflammatory responses in asymptomatic AD (e.g., we previously showed complement activation to accompany the MCI + to AD transition [ 18 ]). Similarly, higher IL-10 levels in AD than NC + and MCI + may represent exaggerated anti-inflammatory responses or appropriate IL-10 response to AD-related neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…However, successful replication of these markers' association with AD has been challenging. This may be due to many issues, including recruitment bias [ 18 ], processing artifacts when assays are performed by commercial vendors [ 19 ], and different antibodies, and few of them have been replicated across cohorts and assay platforms to undergo further standardization and application.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, CD57 that prevents MAC assembly is decreased in AD brain (181). CSF and plasma levels of certain complement proteins have been reported as promising biomarkers for AD diagnosis and progression (182)(183)(184)(185)(186). These observations suggest that activation of the complement system may contribute to the AD pathogenesis.…”
Section: Role Of Complement In Alzheimer's Disease Brainmentioning
confidence: 99%
“…Factor H (FH), the main regulator of this pathway, prevents formation and promotes the dissociation of C3 convertase enzyme (39,40). Several studies have suggested cerebrospinal fluid (CSF) C3 and FH levels could serve as biomarkers for AD and PD (41)(42)(43)(44). According to the alteration of FH expression in neurodegeneration, the expression level of FH was significantly increased in the postmortem brain of AD cases than in the normal elderly (ND) cases (45).…”
Section: Discussionmentioning
confidence: 99%